CLINICAL MANIFESTATION OF COVID-19 CO-INFECTION CASE IN BENGKULU CITY - Debie Rizqoh; Enny Nugrahaeni; Jusup Endang; Mulya Sundari; Dessy Triana; Mardhatillah Sariyanti; Nikki Aldi Massardi (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: The COVID-19 pandemic is still ongoing, and no one could predict when it would end. In some cases of COVID-19, patients experienced infection by SARS-Cov-2 and other microorganisms, including viruses, bacteria, and fungi.Objective: This study aims to determine Co-infection on clinical symptoms and mortality of COVID-19 patients in Bengkulu City, Indonesia.Methods: We reviewed and analyzed data on patients with confirmed COVID-19 who were co-infected, including basic information, clinical manifestations, radiological and laboratory examinations, to the final status.Results: A total of 105 patients with confirmed COVID-19 participated in this study with various clinical manifestation: mild case (12%), moderate case/ mild pneumonia (52%), severe pneumonia (20%) and critical case (16%). Of the 105 patients, six patients were co-infected with human immunodeficiency virus (HIV) (1 case), Mycobacterium tuberculosis (2 cases), Salmonella thypii (2 cases), bacterial pneumonia, and viral pneumonia (1 case). As many as three of the six patients experienced inferior clinical manifestations and died.Conclusion: The co-infection of other microorganisms in COVID-19 can affect the severity and mortality in COVID-19 patients.